Elementary School Teachers in the Island Region of Tual City - Marleny Leasa; Albertus Fenanlampir; John Rafafy Batlolona; Marcy Saartje Ferdinandus (Universitas Negeri Makassar, 2026)
The main problem faced by the partner is that the deep learning approach has not yet been widely implemented by elementary school teachers in Tual City. Most teachers still continue to use surface learning methods that focus mainly on memorization and the delivery of basic information rather than encouraging students to develop critical thinking, creativity, and deeper understanding of the learning material. Consequently, student learning outcomes are still considered less than optimal. Although deep learning (DL) is recognized as an effective approach to improve student comprehension, engagement, and problem-solving abilities, many teachers still lack sufficient knowledge and practical skills to implement it effectively in classroom instruction. Therefore, mentoring activities were conducted to provide teachers with knowledge, understanding, and practical guidance regarding the application of deep learning in teaching and learning processes. This community service (PKM) activity aimed to investigate teachers’ perspectives and understanding of deep learning as well as its implementation in teaching practices. The mentoring method involved assisting teachers in developing instructional materials and presenting the results of their work. The results showed that teachers gained a better understanding of deep learning and became more capable of designing effective DL-based learning materials for classroom use.